1984
DOI: 10.1210/jcem-59-4-705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Pancreatic Tumor Growth Hormone-Releasing Hormone (hpGRHl-44-NH2) on Immunoreactive and Bioactive Plasma Growth Hormone in Normal Young Men*

Abstract: Synthetic human pancreatic tumor GH-releasing hormone (hpGRH 1-44-NH2) was given by iv bolus injection to 10 normal men at doses of 75, 150, 300, and 600 micrograms. At all doses the plasma GH responses were similar in an individual subject. Among subjects, however, the responses were significantly different, with peak GH concentrations ranging between 9.0 micrograms/liter and 54.9 micrograms/liter. The GH released in response to GRH was bioactive in the Nb2 lymphoma cell multiplication assay. The circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…The serum samples were incubated for 18-24 h at 5G3 8C with PRL labelled with 125 I (20 000 cpm/ sample) and in-house rabbit anti-human PRL antibodies (27). These polyclonal antibodies were non-specific for the monomeric form of PRL (28).…”
Section: Assay Methodsmentioning
confidence: 99%
“…The serum samples were incubated for 18-24 h at 5G3 8C with PRL labelled with 125 I (20 000 cpm/ sample) and in-house rabbit anti-human PRL antibodies (27). These polyclonal antibodies were non-specific for the monomeric form of PRL (28).…”
Section: Assay Methodsmentioning
confidence: 99%
“…While these cells might represent trapped normal lactotrophs, their abundance and the clinical observation of a high frequency of hyperprolactinaemia in patients with the ectopic GHRH syndrome (Losa et al, 1993) raise the possibility that chronic exposure to GHRH may also stimulate lactotroph growth. In fact, it has been demonstrated that normal subjects show a rise in PRL after the intravenous administration of larger doses (600 mg) of GHRH (Sassolas et al, 1984). Furthermore, mice transgenic for hGHRH have an increased number of lactotrophs and mammosomatotrophs (Stefaneanu et al, 1989).…”
Section: Morphology Of the Pituitarymentioning
confidence: 99%
“…Additionally, GABAB receptor stimulation may also have a stimulatory effect on serotonin and PRL release (22). Moreover, GHRH increases GH and PRL secretion (41). It is conceivable that SXB stimulates GHRH release and thereby promotes both GH and PRL.…”
Section: Discussionmentioning
confidence: 99%